Determination of adulterants of cocaine in Real banknotes in Brazil by HPLC-DAD - Lópes, Thais (2022)
Cocaine is a tropane alkaloid extracted from coca leaves, a common bush found in Andean regions of South America. Many medicines are added to the final product to increase the profits, keeping similar or higher effects than cocaine alone. Stimulants, anesthetics, and sedatives are the most found adulterants. The goal of this work was to propose a novel analytical methodology to determine cocaine and the main medicines found in street cocaine in Real banknotes using high-performance liquid chromatography with diode array detection (HPLC-DAD). Under optimized conditions, the target substances were extracted with acetonitrile, and the cleanup of the obtained extracts was carried out by separating the fatty layer at low temperature (–20 °C). The volume of extract was reduced under nitrogen flow and adjusted to 2.5 mL with a solution containing 95% (v/v) of phosphate buffer (10 mmol L−1, pH = 2.5) and 5% (v/v) of acetonitrile. Under these conditions, it was possible to identify and quantify cocaine and its adulterants in the samples, with limits of quantification of 0.29, 0.012, 0.16, 0.22, 0.026, 0.078, and 0.14 µg per banknote for acetaminophen, levamisole, caffeine, lidocaine, cocaine, diltiazem, and phenacetin, respectively. We analyzed 158 samples, and only one did not present any of the tested substances. Higher amounts of the tested substances were verified in banknotes of lower value.